Why They Act The Way They Do?: Pedagogical Practices of Experienced Vocational English Language Teachers in Indonesia - Rido, Akhyar (Universitas Negeri Makassar, 2020)
This study was aimed at revealing pedagogical practices of experienced vocational English language teachers, focusing on their lesson planning as well as teaching and classroom management practices, and to understand why they act the way they do. Data were collected through interviews with 5 selected experienced vocational English language teachers and 28 sessions of observations. The results indicated that, in terms of lesson planning practices, they designed potential lesson content from various sources, identified specific linguistic goals, and made appropriate decisions about time sequencing. In terms of teaching practices, they employed a wide variety of techniques (scaffolding, discussion, games, presentation, writing/drawing, and individual task), focused on speaking skills, used handouts, and utilized colourful markers and whiteboard. In terms of classroom management practices, they organized students into groups/pairs, moved around the classroom, arranged classroom in traditional way, addressed misbehaviour, and gave reward and punishment. The pedagogical practices were able to promote effective learning and give positive impact on the students’ behaviour. The results of this study can be used by relevant stakeholders as one of the platforms to understand the current pedagogical practices of experienced vocational English language teachers in Indonesia.